2022
DOI: 10.1002/jssc.202100918
|View full text |Cite
|
Sign up to set email alerts
|

An efficient strategy based on two‐stage chromatography and in vitro evaluation for rapid screening and isolation of acetylcholinesterase inhibitors from Scutellaria baicalensis Georgi

Abstract: The extraction of Scutellaria baicalensis Georgi was investigated using the response surface methodology-genetic algorithm mathematical regression model, and the extraction variables were optimized to maximize the flavonoid yield. Furthermore, a simple and efficient ultrafiltration-liquid chromatography-mass spectrometry and molecular docking methods were developed for the rapid screening and identification of acetylcholinesterase inhibitors present in Scutellaria baicalensis Georgi. Subsequently, four major c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…The longer the arrow is, the greater the contribution of a variable to PC. Therefore, 12 common peaks (1,2,3,4,5,6,8,9,11,12,14,15) were used for the subsequent correlation analysis between chemical components and efficacy.…”
Section: 51mentioning
confidence: 99%
See 2 more Smart Citations
“…The longer the arrow is, the greater the contribution of a variable to PC. Therefore, 12 common peaks (1,2,3,4,5,6,8,9,11,12,14,15) were used for the subsequent correlation analysis between chemical components and efficacy.…”
Section: 51mentioning
confidence: 99%
“…Traditional Chinese medicines (TCMs) or plant-derived compounds have shown multitargeting ability in treating AD. It has been reported that Zanthoxylum nitidum [4], Scutellaria baicalensis [5], and Coptis chinensis [6] exhibit significant inhibitory effects on acetylcholinesterase (AChE) and strong antioxidant activities, becoming great potential protectors of the cholinergic system. Therefore, screening active compounds from TCMs is an important avenue to develop new drugs for multitarget therapy for AD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To screen the active ingredients in the A. membranaceus stems and leaves and assess their bioactivity, a bidirectional approach based on ultrafiltration-LC (UF-LC) with molecular docking validation was proposed [11]. Typically, UF-LC is used to facilitate the separation of ligand-receptor complexes from unbound compounds, and HPLC-MS is subsequently used to identify the ligands [12].…”
Section: Introductionmentioning
confidence: 99%
“…21 In this study, we successfully isolated XODIs with a purity higher than 90% from P. umbellatus using a separate solvent system assisted by the consecutive HSCCC and UNIFAC mathematical models, which further proved that the solvent preparation method could save solvent and contribute to environmental protection. 24 In this study, response surface combined with mathematical BPNN-GA was used to optimise the extraction of P. umbellatus. To demonstrate the drug's activity in treating gout, an efficient method for the rapid screening and purification of potential XODIs from P. umbellatus was established using ultrafiltration combined with enzymatic reaction kinetics, molecular docking, molecular dynamics simulations, and network pharmacology.…”
Section: Introductionmentioning
confidence: 99%